KONTRIBUSI LINGKUNGAN SEKOLAH, KELENGKAPAN FASILITAS DAN MOTIVASI TERHADAP KEDISIPLINAN BELAJAR SISWA SMP - Rizal, Muhammad; Azhari, Azhari (IndOmera, 2023)
This study aims to examine and measure the contribution of school environment, completeness of facilities and student motivation in creating student discipline by studying among students of SMPN 3 Jambo Aye District, North Aceh Regency. This research is a survey on a sample of students, with a quantitative descriptive approach. The analytical method uses the path model. The research results show that 1) there is a correlation between the school environment variable and the facilities of 0.446, and there is a relationship between the facilities variable and the motivation of 0.360 and there is a relationship between the motivation variable and the school environment of 0.427. 2) The results of the hypothesis test show that the contribution of the school environment to student discipline is 14.4%, the contribution of learning facilities to student discipline is 12.29%, and the contribution of learning motivation to student discipline is 19.13%. 3) Simultaneously the school environment, facilities and motivation make a positive contribution to student discipline at SMP Negeri 3 Tanah Jambo Aye Aceh Utara by 55.4%